2008
DOI: 10.1007/s10652-008-9080-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between flow, transport and vegetation spatial structure

Abstract: This paper summarizes recent advances in vegetation hydrodynamics and uses the new concepts to explore not only how vegetation impacts flow and transport, but also how flow feedbacks can influence vegetation spatial structure. Sparse and dense submerged canopies are defined based on the relative contribution of turbulent stress and canopy drag to the momentum balance. In sparse canopies turbulent stress remains elevated within the canopy and suspended sediment concentration is comparable to that in unvegetated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
222
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(260 citation statements)
references
References 73 publications
(104 reference statements)
15
222
0
9
Order By: Relevance
“…9) are similar to s when s/k ≪ 1, and proportional to k when s/k > 0.15 which yields to equation (11). Equation (11) is consistent with literature for shallow cases (Coceal and Belcher, 2004;Nikora et al, 2013) or for deep cases (Ghisalberti and Nepf, 2006;Luhar et al, 2008;Huai et al, 2009;Poggi et al, 2009). For all experiments considered, the averaged error between the experimental and computed (with equation (11)) discharge is about 20% as indicated by the dashlines in Figure 9b.…”
Section: Submerged Conditionssupporting
confidence: 88%
See 1 more Smart Citation
“…9) are similar to s when s/k ≪ 1, and proportional to k when s/k > 0.15 which yields to equation (11). Equation (11) is consistent with literature for shallow cases (Coceal and Belcher, 2004;Nikora et al, 2013) or for deep cases (Ghisalberti and Nepf, 2006;Luhar et al, 2008;Huai et al, 2009;Poggi et al, 2009). For all experiments considered, the averaged error between the experimental and computed (with equation (11)) discharge is about 20% as indicated by the dashlines in Figure 9b.…”
Section: Submerged Conditionssupporting
confidence: 88%
“…The l 0 value can be expressed experimentally using several approaches (Huthoff et al, 2007;Konings et al, 2012;Luhar et al, 2008;Nepf, 2012;Poggi et al, 2009). The present approach is a combination of these formulas in order to use a formula available for a large range of macro-roughness arrangement.…”
Section: Submerged Conditionsmentioning
confidence: 99%
“…This corresponds to a dense canopy (ah > 0.1) for which turbulent sweeps are not expected to penetrate through the entire height of the canopy. 10,45 For comparison, we also considered a completely rigid model canopy with comparable roughness density, h = 13.8 cm, a = 8 m −1 , and ah = 1.1 (run R8 in Ghisalberti and Nepf 14 ).…”
Section: A Experimental Designmentioning
confidence: 99%
“…In addition, the penetration of turbulence through the canopy to the bed determines the likelihood of sediment resuspension, an important feedback to vegetation health. 10,11 Specifically, resuspension negatively impacts light availability for photosynthesis and associated erosion may destabilize shoots. Dense canopies that reduce near-bed turbulence can enhance the supply of nutrients to the plants by promoting the retention of nutrient-rich fine sediment and organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Nehal et al (2005) suggested that overall flow resistance is significantly influenced by the pattern of distribution of the plants. Luhar et al (2008) showed that plant impacts water flow and transport and flow feedbacks influence plant spatial structure. Ye et al (2015) found that plant distribution patterns impact the effects of overland flow resistance.…”
mentioning
confidence: 99%